Penerapan Project Based Learning Berbasis Science Technology Engineering dan Mathematics pada Materi Pertumbuhan - Roselina Lumban Tobing (Pedagogi Hayati, 2021)
The research was conducted at SMAN 4 Tanjungpinang in XII IPA 5 class which aims to describe the steps, learning results and positive impact of STEM-based Project Based Learning (PjBL) model implementation in biology class on growth. This research was conducted from July 12, 2020 to October 30, 2020. The results obtained from this study are the Implementation of STEM Based Learning Project, which can improve the skills of students making experimental reports on learning about Growth of Plants. Based on the data from 2019, the average class score was 63,02. After implementation of STEM-based PjBL in cycle 1 the average class score increase from 75,71 to 83,84. The number of students who didn’t pass the task from cycle 1 are 10 students and the number decreased in cycle 2 to 2 students. The number of students who completed the task increased from 25 to 33 students. The percentage of students who pass the task also increased from 71,42% to 94,28%. Thus, STEM approaches can improve student skills and their understanding of STEM concepts and priciples that can be used integratedly to develop products, processes, and systems that benefit human life.